Ageing of GaN HEMT devices: which degradation indicators?. (January 2016) - Divay, A.; Latry, O.; Duperrier, C.; Temcamani, F.
Abstract: A following of diverse degradation indicators during the ageing in operational conditions of AlGaN/GaN HEMTs (high electron mobility transistors) is proposed. Measurements of pulsed I–V, Schottky barrier height, RF output power and gate current versus output power during the early phase of the ageing test (2000 h on a 6000 h total) are presented. These preliminary results give insight on some of the principal degradation indicators that are interesting to follow during an ageing test close to operational conditions on such components.